A Poetics of Global Solidarity Modern American Poetry and Social Movements - Spahr, Clemens; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2015)
Tackling topics such as globalization and political activism, this book traces engaged poetics in 20th century American poetry. Spahr provides a comprehensive view of activist poetry, starting with the Great Depression and the Harlem Renaissance and moving to the Beats and contemporary writers such as Amiri Baraka and Mark Nowak.
Keywords: Literature; Literature -- History and criticism; Literature, Modern -- 20th century; Poetry; America -- Literatures; Literature; Poetry and Poetics; Twentieth-Century Literature; North American Literature; Literary History; Electronic books